A Review on Pathogenesis and Epidemiology of Coronavirus Disease (Covid-19) - Ul Haq, Mohammed Misbah (Indian Journal of Pharmacy Practice)
Coronavirus disease (COVID-19) is a communicable disease and SARS-COV 2 is the causative agent of a potentially fatal disease this is of exceptional international public fitness concern. Based on the large number of infected people that were exposed to the most animal market in Wuhan City, China, its miles cautioned that this is in all likelihood the zoonotic foundation of COVID-19. Person-to-individual transmission of COVID-19 infection led to the isolation of sufferers that were eventually administered plenty of treatments. Extensive measures to lessen the individual-to-character transmission of COVID-19 were implemented to govern the current outbreak. Special interest and efforts to guard or reduce transmission have to be implemented in susceptible populations which include children, health care providers and elderly people. In this review, the Pathophysiology and Epidemiology of COVID-19 are highlighted.
Keywords: COVID-19; Pathophysiology; Epidemiology; Coronavirus disease 2019; SARS-COV 2.